Are we hitting the target?: The effectiveness of distinct antibiotic regimens in pediatric appendectomies : antimicrobial reports - Elrod, Julia; Yarmal, Fatima; Mohr, Christoph; Dennebaum, Martin Stefan; Boettcher, Michael; Vincent, Deirdre; Reinshagen, Konrad; Koenigs, Ingo (The pediatric infectious disease journal, 2022)
Background: Currently, a range of different antibiotics are administered perioperatively during appendectomy surgery in the pediatric population. One reason for the lack of a uniform treatment regimen is the paucity of large studies on microbiologic data and susceptibility patterns. Methods: A retrospective, monocentric study on antibiotic susceptibility, including 1258 pediatric patients undergoing appendectomy from 2012 to 2020 was performed. Predictors for prolonged length of stay (LOS) and complications were determined using regression analysis, and objective criteria for broad-spectrum antibiotic regimens were identified. Simulations of the effectiveness of different antibiotic regimens against identified bacterial susceptibility results were conducted. Results: The most important predictors for prolonged LOS and an increased incidence of infectious complications are elevated preoperative C-reactive protein levels, high intraoperative severity gradings and insufficient primary antibiotic treatment. Based on our results, a simple antibiotic treatment, consisting of cefuroxime-metronidazole (C-M) or ampicillin-sulbactam (AS), is sufficient in around 85% of all patients; both options being equally efficient. In severe appendicitis, the likelihood of resistance is 31% and 32% for C-M and AS, respectively. For piperacillin-tazobactam and C-M-tobramycin, the incidence of bacterial resistance decreases to 12%. Resistance is reduced to 8% for AS-tobramycin treatment. The patient populations benefiting most from an extended antibiotic regimen are those with a high intraoperative severity grading. Conclusions: Evidence suggests that an insufficient antibiotic regimen is associated with a prolonged LOS and a higher rate of infectious complications, justifying the expansion of a simple antibiotic regimen in cases of severe intraabdominal findings. In all other cases, a simple antibiotic treatment with AS is recommended.
Gesehen am 09.01.2024